Pengaruh Insentif, Motivasi Kerja Dan Komitmen Organisasi Terhadap Kinerja Anggota Karang Taruna Karsa Bhirawa - Vriske Iga Sistian; Budi Wahono; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The aim of this type of explanatory research and quantitative approach is to identify and analyze the effect of incentives, work motivation and organizational commitment on member performance, either simultaneously or partially. Sampling used a saturated sampling technique where all members of the population were sampled so that 50 respondents were obtained, which is the total number of members of Karang Taruna Karsa Bhirawa. This research method uses multiple linear regression analysis with the SPSS analysis tool. Based on the results of this study that the effect of incentives, work motivation and organizational commitment simultaneously have an influence on member performance. Tests carried out with partial tests show that the variables of incentives and work motivation have a positive and significant influence. Meanwhile, the organizational commitment variable has a positive and insignificant effect Keywords: Karang Taruna, Incentives, Work Motivation, Organizational Commitment, Member Performance